PENGARUH PENERAPAN FUNGSI PENGAWASAN TERHADAP DISIPLIN KERJA PEGAWAI PADA KANTOR KECAMATAN GALELA KABUPATEN HALMAHERA UTARA - Gosango, Linda (Sam Ratulangi University, 2013)
Abstract : Research in the preparation of the thesis Tahir degree ( S1 ) departs from the observation that the employees at the District Office Galela North Halmahera has not shown that the optimal behavior of labor discipline , it is something to do with the application fungsinpengawasan by the leader ( Head ) are less strict . Thus , this study aimed to analyze the effect of the application of the oversight function of the discipline employee working at the district office Galela North Halmahera .Methods and approaches used in this study is a quantitative and explanatory , where the data were collected through questionnaires distributed instruments to 30 employees at the district office Galela , after the data is collected , then analyzed dngan applying simple regression analysis techniques and product moment correlation .The results showed that the average implementation oversight functions performed by the leadership , especially in the sub-district office Galela North Halmahera district has not been optimal . Not optimal implementation oversight by district Galela and this is a negative effect of the limited scope of authority that led to an attitude of doubt in taking action . The conclusion that can be drawn from these results is that the oversight function by Head penerapn very significant or noticeable effect on employee discipline at the district office Galela North Halmahera district . For that to district needs to improve oversight , especially effective monitoring instruments attached . In addition, the instrument needs to diefektifkn rewards , both pemeberian awards for employees who commit disciplinary offenses.Keyword : controlling, working discipline